Element release and reaction-induced porosity alteration during shale-hydraulic fracturing fluid interactions. (July 2017) - Harrison, Anna L.; Jew, Adam D.; Dustin, Megan K.; Thomas, Dana L.; Joe-Wong, Claresta M.; Bargar, John R.; Johnson, Natalie; Brown, Gordon E.; Maher, Katharine
Abstract: The use of hydraulic fracturing techniques to extract oil and gas from low permeability shale reservoirs has increased significantly in recent years. During hydraulic fracturing, large volumes of water, often acidic and oxic, are injected into shale formations. This drives fluid-rock interaction that can release metal contaminants ( e.g., U, Pb) and alter the permeability of the rock, impacting the transport and recovery of water, hydrocarbons, and contaminants. To identify the key geochemical processes that occur upon exposure of shales to hydraulic fracturing fluid, we investigated the chemical interaction of hydraulic fracturing fluids with a variety of shales of different mineralogical texture and composition. Batch reactor experiments revealed that the dissolution of both pyrite and carbonate minerals occurred rapidly, releasing metal contaminants and generating porosity. Oxidation of pyrite and aqueous Fe drove precipitation of Fe(III)-(oxy)hydroxides that attenuated the release of these contaminants via co-precipitation and/or adsorption. The precipitation of these (oxy)hydroxides appeared to limit the extent of pyrite reaction. Enhanced removal of metals and contaminants in reactors with higher fluid pH was inferred to reflect increased Fe-(oxy)hydroxide precipitation associated with more rapid aqueous Fe(II) oxidation. The precipitation of both Al- and Fe-bearing phases revealed the potential for the occlusion of pores and fracture apertures, whereas the selective dissolution of calcite generated porosity. These pore-scale alterations of shale texture and the cycling of contaminants indicate that chemical interactions between shales and hydraulic fracturing fluids may exert an important control on the efficiency of hydraulic fracturing operations and the quality of water recovered at the surface. Highlights: Chemical interactions influence unconventional hydrocarbon recovery and water quality. Fracturing fluid drives dissolution of carbonates and iron sulfides. Mineral dissolution releases contaminants to solution and generates porosity. Fe-bearing precipitates attenuate released contaminants but occlude porosity.